Agrobacterium-mediated barley transformation - Éva, Csaba; Csóti, István; Tamás, László (Acta Biologica Szegediensis, 2008)
More than ten years have passed since the first successful Agrobacterium-mediated barley transformation experiment, however it is still quite challenging to establish a stably functioning agroinfiltration protocol. Efficiency of the method depends mainly on the transformation and co-cultivation conditions, and also the components of the tissue-culture media. With the use of an optimized media we have been able to set up a reliable, properly functioning transformation protocol. The first generation of transgenic barley plants, transformed with a transformation cassette carrying an aldo-keto-reductase gene from Arabidopsis thaliana and the hpt marker gene, were analyzed at nucleic acid (both DNA and RNA) and at protein levels. The key factors of success proved to be the use of Silwet L-77 (surfactant) in transformation inoculum, the Cu-content of regenerating media and the continuous visual monitoring of the transformed callus during the somatic embryogenesis.